Liquidity and Transparency in Bank Risk Management - Ratnovski, Lev (IMF Working Papers; Working Paper ;, 2013)
Banks may be unable to refinance short-term liabilities in case of solvency concerns. To manage this risk, banks can accumulate a buffer of liquid assets, or strengthen transparency to communicate solvency. While a liquidity buffer provides complete insurance against small shocks, transparency covers also large shocks but imperfectly. Due to leverage, an unregulated bank may choose insufficient liquidity buffers and transparency. The regulatory response is constained: while liquidity buffers can be imposed, transparency is not verifiable. Moreover, liquidity requirements can compromise banks' transparency choices, and increase refinancing risk. To be effective, liquidity requirements should be complemented by measures that increase bank incentives to adopt transparency.